Thermal decomposition of solid state compounds of lanthanide and yttrium benzoates in CO2 atmosphere - Locatelli, J. R.; Siqueira, A. B. [UNESP]; Carvalho, C. T. [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2008)
Foram sintetizados no estado sólido os compostos Ln-Bz, onde Ln representa lantanídeos trivalentes e Bz benzoato. Análise termogravimétrica e análise térmica diferencial (TG/DTA) foi usada para estudar a decomposição térmica destes compostos em atmosfera de CO2.

Solid-state Ln-Bz compounds, where Ln stands for trivalent lanthanides and Bz is benzoate have been synthesized. Simultaneous thermogravimetric and differential thermal analysis in a CO2 atmosphere were used to study the thermal decomposition of these compounds.
Decomposição térmica dos benzoatos de lantanídeos e ítrio no estado sólido em atmosfera de CO2
Keywords: lantanídeos; benzoato; decomposição térmica; atmosfera de CO2; lanthanides; benzoate; thermal decomposition; CO2 atmosphere